Junho 2022 (Abstracta, 2022)
Artigos publicados - P077-2022 à P133-2022Correções - C003-2022 à C004-2022Defesas de Dissertações do IFGW - D006-2022 à D012-2022Defesas de Teses do IFGW - T009-2022 à T010-2022